Epithelial Membrane Protein 1 Promotes Sensitivity to RSL3-Induced Ferroptosis and Intensifies Gefitinib Resistance in Head and Neck Cancer. (6th April 2022) - Wang, Ying; Zhang, Liang; Yao, Changyu; Ma, Yunxia; Liu, Yehai
Abstract : Epithelial membrane protein (EMP1), a member of the peripheral myelin protein (PMP22) family, is involved in the development of various human malignancies. However, the expression level of EMP1 and its functional role in head and neck squamous cell carcinoma (HNSCC) remain unclear to date. Ferroptosis, a newly characterized form of regulated cell death, plays an essential role in tumorigenesis. In this study, we aimed to investigate the expression levels of EMP1 in HNSCC and normal tissues, as well as to identify the function of EMP1 in regulating ferroptosis during the progression of HNSCC. To further explore the biological function of EMP1 in vitro, transient transfection was used to overexpress EMP1 in the HNSCC cell lines Hep2 and Detroit562. Functionally, our results indicated that EMP1 overexpression could not affect the initiation of ferroptosis directly but reinforced RSL3-induced ferroptosis on HNSCC cells. Furthermore, mechanical study indicated that EMP1 mediated the ferroptosis via cell density-regulated Hippo-TAZ pathway and regulated the expression of Rac1 and NOX1. In addition, our study demonstrated that EMP1 overexpression could promote gefitinib resistance by targeting the MAPK pathway. In summary, our findings indicate that EMP1 may act as an oncogene and serve as a therapeutic target against malignant progression of HNSCC.